Can the laser‐cut covered self‐expandable metallic stent be the first choice for patients with unresectable distal malignant biliary obstruction? (with video). (25th August 2021) - Tanisaka, Yuki; Mizuide, Masafumi; Fujita, Akashi; Ogawa, Tomoya; Katsuda, Hiromune; Saito, Youichi; Miyaguchi, Kazuya; Araki, Ryuichiro; Ryozawa, Shomei
Abstract: Objectives: To evaluate whether laser‐cut covered self‐expandable metallic stents (LC‐CSEMSs) can be the first choice for patients with unresectable distal malignant biliary obstruction (DMBO). Methods: Patients with unresectable DMBO who received LC‐CSEMS (September 2014‐December 2020) or braided CSEMS (B‐CSEMS) (July 2013‐December 2020) placement for biliary drainage were enrolled. Outcomes, including endoscopic CSEMS removal, of LC‐CSEMSs and B‐CSEMSs were compared. Results: Overall, 124 patients received LC‐CSEMSs placement, and 121 B‐CSEMSs. Technical success, clinical success, and procedure‐related adverse event rates with LC‐CSEMSs were 100%, 96.8%, and 6.5%, respectively, and 100%, 95.9%, and 5.8%, respectively, for B‐CSEMSs, with no significant difference ( P  > .99, .75, and >.99, respectively). The recurrent biliary obstruction (RBO) rates with LC‐CSEMSs and B‐CSEMSs were 9.7% (12/124) and 13.2% (16/121), respectively ( P  = .43). The median time to RBO with LC‐CSEMSs and B‐CSEMSs was 198 (interquartile range [IQR], 124‐244) days and 191 (IQR, 106‐271) days ( P  = .41). The endoscopic removal success rates of LC‐CSEMSs and B‐CSEMSs were 88.9% (8/9) and 90% (9/10) ( P  > .99), although there were a small number of cases. Conclusions: The non‐inferiority of LC‐CSEMSs was proven. LC‐CSEMSs can be considered as the first choice for patients with unresectable DMBO. Abstract : Highlight Covered self‐expandable metallic stents are widely used for unresectable distal malignant biliary obstruction. Tanisaka and colleagues proved the non‐inferiority of the laser‐cut versus the braided covered self‐expandable metallic stent, including for stent removal. Minimal shortening and ease of placement may make it the first choice for unresectable distal malignant biliary obstruction.